The Effects of Spiritual Leadership on Organizational Citizenship Behaviour in Universiti Kuala Lumpur Business School - Uchechukwu, Otuokere Godswill (Human Resource and Leadership Journal, 2025)
Purpose: Although research on spiritual leadership is clearly still emerging, there is little doubt that this form of leadership contains desirable qualities that many organizations might consider for their best interest. The objective of this study is to assess the effects of spiritual leadership on organizational citizenship behaviour in Universiti Kuala Lumpur Business School and MIIT all in Malaysia. Methodology: Survey design was adopted. Data were collected through questionnaire. A sample size of 143 were used comprising of academic staff of Universiti Kuala Lumpur, Malaysia. Analysis was carried out using Pearson Moment and regression method of statistical tool. Findings: This study found that spiritual leadership positively and significantly affects organizational citizenship behaviour. The more high level of spiritual leadership, especially in terms of clear vision, hope/faith and altruistic love, the more advanced of employees’ behaviour and satisfaction. Spiritual leadership creates congruence across the empowered team to foster increased level of productivity and performance. Unique Contribution to Theory, Practice and Policy: The study suggests that top management at Universiti Kuala Lumpur Business School and MIIT in Malaysia should review employees' organizational citizenship behavior to enhance spiritual leadership style. This will lead to higher understanding, honesty, and commitment, resulting in better job performance, better relationships, and better acceptance of organizational objectives. The findings can be applied to other organizations striving for high leadership standards.